On the peculiarities of lexic in oral and written use (by q -frequency lists of the materials of mass media) (Eurasian Journal of Philology Science and Education, 2016)
The article talks about the frequency research for the Kazakh language, conducted on materials written and oral texts in the mass media. Generated frequency lists created on base of written and oral texts: interviews, talk shows, written notes, responses to questions, etc. Since the main parameter of differentiation in this case is the form of the Kazakh communication – oral or written. This article also includes two frequency vocabulary what demonstrates the specific on example of 100 the first high-ranking frequency units. The article’s material describes this specificity of each type of frequency dictionary. Moreover, this paper says about the use of frequency lists for Kazakh language teaching, about indexing Kazakh texts for scientometric search, about the use in the Kazakh linguistics and IT development for the natural language.
Keywords: frequency dictionary; Kazakh language; mass media.